Exploring the likelihood of the formation of Organization of Rice Exporting Countries in international rice market - Kulyadul, Supaluck (2008)
The situation in international rice trade can be considered as in crisis because of two main factors; an increase in rice prices and shortage of rice supply. The rice crisis has impacts on rice producers, traders, consumers in terms of life quality, especially those in Asia where rice is considered a basic staple and necessary commodity. To alleviate negative consequences from the crisis, an idea to stabilize international rice market is to form a rice cartel called Organization of Rice Exporting Countries (OREC). The objectives are to enforce control over international rice prices, to prevent rice shortage and to exchange information about food stability. So far, Thailand, Burma and Laos agree with this idea while Vietnam is still considering.